Adoção de tecnologia no combate a violência contra a mulher no âmbito da segurança pública de Santa Maria - Bastianello, Cleberson Braida (2023)
The present study found that violence against women is linked to historical and cultural factors, while this phenomenon of “patriarchy” has long been rooted in society. This time, technology has been innovating in the sense that it is increasingly present in society's daily life, and for this reason, the development of various devices to report cases of violence against women has been growing abruptly and being used for the prevention of domestic violence. Based on this information collected, through the project known as “Todas Nós Marias”, an attempt was made to launch a security device, through the use of the Application, on a cell phone, in order to help women in situations of domestic violence. The research sought to verify its effectiveness, considering its scope, use and safety for women, regarding the development and effectiveness of the Urgent Protective Measures - MPU, established with the aim of preserving the physical, psychological and moral integrity of women in situations of domestic and family violence, according to Law 11.340/2016, known as the Maria da Penha Law, in particular the “Panic Button”, adopted by the CIOSP of Santa Maria/RS. Finally, it can be briefly concluded that, although the degree of effectiveness of the Panic Button cannot be affirmed, this can be considered a promising practice, since it gave women a sense of security. However, there is a need for further study and monitoring, as well as investment by the Government, so that society can use the tool on screen.